Design Of Safety Signs Using Ergonomic Function Deployment Method At PT.XYZ - Dita Kusuma Ningsih; Heriyono Lalu; Sheila Amalia Salma (International Journal of Innovation in Enterprise System, 2022)
PT. XYZ is a company engaged in manufacturing by processing raw materials into semi-finishedgoods or finished goods. Because the company routinely produces these products and involvesmachinery, it will allow small to serious work accidents to occur. Based on the hazard event dataowned by the company, there are 5 very diverse events that will be analyzed in the risk controlhierarchy to minimize hazard events. The results of the risk control hierarchy analysis have two hazardevents that have safety sign design criteria. Therefore, research was conducted to design safety signsin the area of explosive materials and loading progress in minimizing hazard events using safety signsassessment and Ergonomic Function Deployment approaches. The data needed in the design areanthropometric data, layout data, customer statements and level questionnaires interest andsatisfaction. From the results of the safe sign assessment, the signal word is obtained, determining thelocation, height, model, and material of the safety signs. The results of the safety signs assessmentwill be used for the Ergonomic Function Deployment approach. From the results of the ErgonomicFunction Deployment, the results obtained are the size of safety signs, safe reading distance, type oflayout, use of language and font size on safety signs. There are two types of designs, namely explosivematerial and loading progress safety signs. The design of safety signs refers to the ANSI Z535standard so that the design of safety signs has detailed signal words, symbols, signs, and wordmessages.